Urgensi Peranan Keluarga bagi Perkembangan Self-esteem Remaja - Nikmarijal Nikmarijal; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
Adolescence is the period of interest due to their properties and its role in determining the life of society. The one that affects its development is self-esteem. Self-esteem is formed through the interaction of individuals with their environment. One family environment, if the environment providing something fun, self-esteem would be positive, but if its not fun and self-esteem will be negative, further support parents, parental control, and relationship to each other between the parents give a direct influence on the development of adolescent self-esteem. This article will expose further the importance of the role of the family in developing the self-esteem of teenage.